2005
DOI: 10.1007/s11178-005-0370-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of β-Aminophosphonates and Study of Their Acid-Base Properties and Phase Distribution in Water-Organic Solvent Systems

Abstract: New and previously known -aminoethylphosphonates were synthesized by addition of primary and secondary amines to vinylphosphonates, and their IR and NMR spectra were examined. Diethyl 2-diethylaminoethylphosphonate and diethyl 2-morpholinoethylphosphonate were found to be stronger bases than the corresponding aminomethylphosphonates, but all these are weaker bases than their precursors, nonphosphorylated amines. Distribution constants of -aminophosphonates between water and some organic solvents were determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…[47] However, the mechanism is more complicated than it appears in Scheme 15 since the nature of ketone, [47] the activator, [48] the solvent, [49] and the PK b of the amine [50] all have an effect. Several studies could prove that path A is the most convenient pathway.…”
Section: (A) Pudovik Reactionmentioning
confidence: 99%
“…[47] However, the mechanism is more complicated than it appears in Scheme 15 since the nature of ketone, [47] the activator, [48] the solvent, [49] and the PK b of the amine [50] all have an effect. Several studies could prove that path A is the most convenient pathway.…”
Section: (A) Pudovik Reactionmentioning
confidence: 99%
“…Pudovik and Denisova first showed that ammonia adds to diethyl vinylphosphonate in the presence of EtONa in the normal manner (Scheme 5.34) [146]. The reaction with primary amines is usually activated by basic catalysts under heating [147]; secondary amines add to the vinylphosphonate easily without a catalyst, whereas aniline reacts only in the presence of MeONa and with only a fair yield [148].…”
Section: Synthesis Of B-aminophosphonatesmentioning
confidence: 99%
“…9 Later on, different approaches were explored. [10][11][12][13] The most practical approach was developed by Odinets et al, 14 which was then followed by others. 15,16 According to this, primary or secondary amines may be added to the double bond of dialkyl vinylphosphonates in water as the medium in the absence of any catalyst.…”
Section: Introductionmentioning
confidence: 99%